Legal Obligations of Telegram Users Regarding Copyrighted Content Distribution in Public Groups: Kewajiban Hukum Pengguna Telegram Terkait Distribusi Konten Berhak Cipta di Grup Publik - Visa, Hikmah Tara Widya; Multazam, Mochammad Tanzil (Indonesian Journal of Law and Economics Review, 2024)
In the digital era, copyright infringement poses a significant challenge, particularly on platforms like Telegram, where communication and content sharing are prevalent. This study employs a normative juridical method with a statutory approach to analyze the implications of copyright infringement facilitated by Telegram groups. Through deductive analysis, the research reveals the legal consequences of re-uploading copyrighted content in public or non-specifically designated groups on the platform, notably in violation of Law No. 28 of 2014 concerning Copyright. The findings underscore the responsibility of users for sharing copyrighted material without permission, emphasizing the need for adherence to legal provisions. Highlights : The study delves into the legal ramifications of copyright infringement within Telegram groups. Using a normative juridical method, it highlights the responsibility of users for sharing copyrighted content. The research underscores the importance of adhering to applicable copyright laws in digital communication platforms like Telegram. Keywords: Copyright infringement, Telegram groups, Legal consequences, Normative juridical analysis, Statutory approach